Gambaran Depresi dan Kecemasan Pada Pasien Kanker Serviks - Nurul Hafiza; Fathra Annis Nauli; Ade Dilaruri (Jurnal Ilmiah Wahana Pendidikan, 2023)
Cervical cancer is one of the most common types of cancer among women. In addition to experiencing physical problems, cervical cancer sufferers tend to experience anxiety and depression. The purpose of this study was to describe depression and anxiety in cervical cancer patients at Arifin Achmad Hospital. This research is a descriptive research design using purposive sampling technique. The research sample consisted of 75 respondents with inclusion and exclusion criteria. Data collection method using DASS-21 questionnaire. The analysis used is univariate analysis, which is displayed in the form of a frequency distribution table. The results showed that most of the respondents aged 46- 55 years were 31 people (41.3%), the education level of the majority of respondents was high school 38 people (50.7%), most of them worked as housewives 58 people (77.3% ), the most respondents were stage III 32 people (42.7%), long diagnosed with cancer 0-1 years 58 people (77.3%), the majority of treatment was chemotherapy 27 people (36%), the level of depression category the majority was normal 63 people (84%) and anxiety category majority was normal 40 people (53.3%). From this study it can be concluded that cervical cancer can cause depression and anxiety from mild to very severe categories. Therefore, nursing interventions that can reduce depression and anxiety in cervical cancer patients must be carried out by nurses.